Strategies For Developing Islamic Education To Strengthen Religious Moderation: A Case Study Of The Ministry Of Religious Affairs In Karawang Regency - Maehi, Emay Ahmad; Kosim, Abdul; Nur, Tajuddin (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to analyze strategies for developing Islamic education in strengthening religious moderation at the Ministry of Religious Affairs of Karawang Regency. This study uses a qualitative approach with a case study design through observation, in-depth interviews, and documentation studies. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, and conclusion drawing. The resultsof the study show four main strategies that are the focus of strengthening religious moderation, namely strengthening internal policies as the basis for program implementation, increasing the capacity of teachers and educational personnel through training and workshops, integrating moderate values into the curriculum and learning activities, and expanding partnerships with various educational institutions and community organizations. In addition, this study identified supporting factors in the form of institutional commitment, the existence of national guidelines on religious moderation, and an increase in teachers' interest in improving their competence. The obstacles found include limited human resources, variations in teachers' understanding of the concept of moderation, and local socio-cultural challenges that affect policy implementation at the educational unit level. These findings confirm that targeted, adaptive, and collaboration-based strategies can strengthen the internalization of religious moderation in Islamic education environments. As a result, this study provides practical recommendations for regional Ministries of Religious Affairs to strengthen context-based training designs, develop religious moderation evaluation instruments, and expand strategic partnerships to improve program effectiveness in a sustainable manner.